(untitled) (Revista de Estudos da Linguagem, 2025)
Since the United Nations Agenda 2030 was set up, many countries have worked to find solutions to interconnected global issues such as hunger, poverty, education and sustainability just to mention a few. After the striking of COVID-19 pandemic, the world witnessed researchers gathering around in an international effort to find solutions to the problems previously pointed out. In order to describe the lexis used in research papers discussing the Sustainable Development Goals (SDGs), we compiled a 2 million-word corpus from the PLOs platform with the AntCorGen program using the query term “Sustainable Development Goal”. After that, we part of speech-tagged the corpus using the Tree-tagger of Sketch Engine in order to carry out a lexical multidimensional analysis (LMDA). Our aim was to (i) identify the major dimensions of variation based on the lexico-grammatical characteristics in research papers published in English by international researchers and (ii) observe how the SDG themes stand out in the study corpus. Results showed six dimensions that were named according to the words concentrated in each one: Government Actions, Presenting Results, Data Interpretation, Data Presentation, Data Quality, Research Procedure. The first dimension is the one that best illustrates a theme related to the SDGs whereas the other five dimensions clearly show the lexis that illustrates how researchers describe their own articles.